A 3D finite element model to predict the arcade-like collagen structure in a layered PCL scaffold for cartilage tissue engineering - Cortez, Sara (2018)
Recently, tissue engineering strategies have been increased in order to mimic as closely as possible the environment of the native tissue, improving the regeneration of its structure and function. Previous experiments of cartilage tissue engineering used scaffolds with a homogeneous structure. However, the zonal organization in constructs has been shown to develop functional tissues with better biomechanical and biochemical properties. McCullen et al. (2012) studied the scaffold with a trilaminar structure of fibres showed that the heterogeneous organization have superior features when compared with the homogeneous scaffolds. Similarly, Steele et al. 2014 demonstrate that bilayered cartilage scaffolds have zonal differences in cellular proliferation, biochemical composition and gene expression. The directional organization of collagen fibres in the scaffolds strongly influences the anisotropic mechanical behaviour of the tissue, since the collagen fibres are the major responsible for its mechanical strength. The main goal of this study is to present new results related with a new anisotropic finite element (FE) model to mimic the growth and the remodelling of collagen fibres in a zonal organized polycaprolactone (PCL) scaffold for cartilage tissue engineering.